Complex and severe infection in a 67-year-old liver transplant recipient due to Cunninghamella elegans, Bordetella bronchiseptica, and Pneumocystis jirovecii - Muyun Wei; Kangyi Gu; Juanxiu Qin; Xinhua Lu; Junqi Feng; Shaowei Mao; Min Li; Zhilan Li; Changsheng Wang (BMC Infectious Diseases)
Abstract Introduction Cunninghamella elegans infections cause rare and severe mucormycosis. Bordetella bronchiseptica and Pneumocystis jirovecii relate to pneumonia. They are all clinically uncommon pathogens and no reports of co-infections have been reported. Case presentation Here we present a case of a 67-year-old male patient who initially presented with fever, chills, and mild cough. B. bronchiseptica, P. jirovecii, Aspergillus fumigatus, and human alphaherpesvirus 1 (HSV1) were detected by clinical metagenomic next-generation sequencing (mNGS) of his bronchoalveolar lavage fluid (BLAF). Despite receiving anti-infective treatment, the patient rapidly developed respiratory failure and was transferred to the intensive care unit. Subsequent mNGS testing further revealed the presence of C. elegans, indicating that different pathogens played dominant roles at various stages of the disease progression. The routine culture also identified several of the above pathogens, but the results were reported much later than those of mNGS. Eventually, imaging findings and symptoms of the patient improved with comprehensive antibiotic coverage, and he was transferred to a lower-level hospital for rehabilitation treatment. Conclusions This is the first detailed report of the combined infection of B. bronchiseptica, P. jirovecii, and C. elegans. During the treatment process, we also observed rare and unusual neurological side effects: visual and auditory hallucinations, restlessness, and aphasia. Also, the case indicates that traditional methods are insufficient for the etiological diagnosis needs of critical and severe patient populations, and timely use of mNGS should be recommended.